Structural–functional coupling abnormalities in temporal lobe epilepsy - Huang, Xiaoting; Du, Yangsa; Guo, Danni; Xie, Fangfang; Zhou, Chunyao (Frontiers in Neuroscience, 2023)
We aimed to evaluate the coupling of structural connectivity (SC) and functional connectivity (FC) in the entire brain of healthy controls (HCs), and to investigate modifications in SC-FC coupling in individuals suffering from temporal lobe epilepsy (TLE). First, the SC-FC coupling between regions was determined, based on which whole-brain nodes were clustered. Differences in the coupling among the three groups of nodes were compared. To further validate the results obtained, the within-module coupling indices of the three groups were compared to determine the inter-group differences. Nodes were divided into five clusters. Cluster 1 was primarily located in the limbic system (n = 9/27), whereas cluster 5 was mainly within the visual network (n = 12/29). The SC-FC coupling of nodes in individuals with TLE showed a significantly reduced level compared to those in HCs in clusters 3, 4, and 5. We also observed that the within-module SC-FC coupling in cluster 5 of left-and right TLE was significantly lower than in HCs. The SC and FC in HCs exhibited obvious high coupling, whereas patients with TLE exhibited decoupling. The brain regions with high coupling in HCs were more prone to damage in participants with TLE.